Anaphora processing : linguistic, cognitive, and computational modelling - Branco, Antonio; McEnery, Tony, 1964-; Mitkov, Ruslan (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2005)
Anaphora processing is a central topic in the study of natural language and has long been the object of research in a wide range of disciplines. The correct interpretation of anaphora has also become increasingly important for real-world natural language processing applications, including machine translation, automatic abstracting, information extraction and question answering. This volume provides a unique overview of the processing of anaphora from a multi- and inter-disciplinary angle. It will be of interest and practical use to readers from fields as diverse as theoretical linguistics.